Penerapan Standar Akuntansi Keuangan EMKM Pada Laporan Laba Rugi di Kedai Hobi Kopi Kecamatan Ambulu Kabupaten Jember - Setiawan, M. Erik; Lestari, Hari Budi; Susanto, Andri Mardi (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2024)
SAK EMKM is used by entities that do not or have not been able to fulfill the accounting requirements regulated in SAK ETAP. In SAK EMKM, the entity's financial statements are prepared using basic accrual and business continuity assumptions, as used by micro, small and medium entities and using the business entity concept. This research aims to determine the application of SAK EMKM to the profit and loss report at the